Detecção de contradições em um sistema de aprendizado sem fim - Oliverio, Vinicius (2012)
NELL (Never Ending Language Learning) is a system that seeks to learn in an infinite way, extracting structured information from unstructured web pages using the semi-supervised learning paradigm as one of its basic principles. The Read the Web (RTW) project is the project where the NELL system is contained, actually it consists of 5 modules, all of them working independently where one of the modules is called Rule Learner (RL). The RL is responsible for inducing first order rules, which are used by the system to identify patterns in the knowledge generated by the other four components of the system. These rules are induced and then represented in a syntax that has Horn clauses as base. These rules can present contradictions, and in this context this paper proposes investigate, develop and implement methods to detect and solve these contradictions so that the system can learn in a more efficient way